Analisis Kesesuaian Lahan Permukiman Terhadap Kerawanan Bencana di Kecamatan Cilongok Kabupaten Banyumas - Fadinaldi, Muhammad Ibnu, Agus Anggoro Sigit, S. Si, M. Sc (2017)
Land suitablty settlement to vulnerability disaster is very important to prevent danger development in areas according to due population growth that is increasing .Mapping land suitablity to settlement know distribution land suitabilty settlement in research areas and to know distribution vulnerability disaster in the research areas. Methods that used to analysis is SIG with the methods quantitative tiered to produce map land suitabilty settlement. Every parameter used given a score. Parameter that used in this research are rainfall , slope slope , the type of land and vulnerability disaster . The result of this research is direction the region and land suitablity settlements in subdistrict Cilongok. Direction the region include Protection Area with area of 3829 ha (29%), Buffer Area 3253 ha (24%), and Cultivation Area 6353 ha (47%). Land suitabilty settlements that is divided into to 5 classes appropriate for settlement (S1), appropriate for settlement obstacles low (S1), appropriate for settlement obstacles medium enterprises ( S3 ), almost not appropriate for settlement ( N2 ), and not based to settlement ( N3 ). The appropriate areas for a settlement is in some region of research with widely 7943 hectare. While the areas that aren't appropriate to the settlement have widely 3829 hectare.